Modeling and Evolving Crosscutting Concerns in ADORA - Meier, Silvio; Reinhard, Tobias; Stoiber, Reinhard; Glinz, Martin (Proceedings of the Early Aspects at ICSE : Workshops in Aspect-Oriented Requirements Engineering and Architecture Design, 2007)
For an effective handling of crosscutting concerns during the software process, adequate support is required not only in design and coding, but also in requirements engineering. For this purpose, we have developed an aspectoriented extension of the requirements modeling language ADORA. In this paper, we present an extension of our approach which makes it capable of supporting the evolution of aspect-oriented requirements models for both functional and non-functional aspects.